Bioresearch of New 1H-pyrrolo[3,4-c]pyridine-1,3(2H)-diones - Dominika Szkatuła; Edward Krzyżak; Szczepan Mogilski; Jacek Sapa; Barbara Filipek; Piotr Świątek (Molecules, 2020)
The subject of the work was the synthesis of new derivatives of1H-pyrrolo[3,4-c]pyridine-1,3(2H)-dione with potential analgesic and sedative activity. Eight compounds werereceived. The analgesic activity of the new compounds was confirmed in the “hot plate” test and in the “writhing” test. All tested imides 8–15 were more active in the “writhing” test than aspirin, and two of them, 9 and 11, were similar to morphine. In addition, all of the new imides inhibited the locomotor activity in mice to a statistically significant extent, and two of them also prolonged the duration of thiopental sleep.On the basis of the results obtained for the previously synthesized imides and the results presented in this paper, an attempt was madeto determine the relationship between thechemical structure of imides and their analgesic and sedativeproperties.